Students' Perception on the Role of English Day Program in Speaking Skill Development - Sinaga, Octovany (JET (Journal of English Teaching), 2018)
This study aims to investigate students’ perceptions of English Day Program in speaking skill development. To achieve the objective, a questionnaire and interview were administered to collect the perception of 35 eight graders of SMPK Penabur Kota Wisata, Bogor. The quantitative data collected by the questionnaire and the qualitative data obtained from the interview were analyzed employing the descriptive analysis technique. The results showed that students' motivation to master English speaking was very high, and they expected the English Day Program would help them develop English speaking. However, only slightly more a half of them were enthusiastic to join English Day Program due to its previous poor implementation.